Phytochemistry of Trattinnickia burserifolia, T. rhoifolia, and Dacryodes hopkinsii: Chemosystematic implications - Lima, Maria da Paz (2004)
Trattinnickia burserifolia has yielded the known ursanes, α-amyrenone, α-amyrin, 3-epi-α-amyrin, 3α,16β- dihydroxyurs-12-ene, the oleananes β-amyrenone, β-amyrin, 3-epi-β-amyrin, 3α,16β-dihydroxyolean-12-ene, the tirucallane acids 3α-hydroxytirucall-8,24-dien-21-oic, 3α-hydroxytirucall-7,24- dien-21-oic and 3-oxotirucall-8,24-dien-21-oic, the dammaranes dammarenediol-II and 3α,20(S)-dihydroxydammar-24-ene. Besides it was isolated the new monoterpene 2(S*)-phenylacetoxy-4(R*)-p-mentha-1(7),5-diene and, the new triterpenes 3β-phenylacetoxyurs-12-ene, 3β-phenylacetoxyolean-12- ene and 3β,16β,11α-trihydroxyurs-12-ene. The triterpenes from T. burserifolia, T. rhoifolia and Dacryodes were analyzed in mixture. Their 13C NMR spectra showed that the major triterpenes were in T. burserifolia α-amyrin and β-amyrin; in T. rhoifolia α-amyrin, β-amyrin, 3-epi-α-amyrin, 3-epi-β-amyrin, and lupenone; in T. rhoifolia α-amyrin, β-amyrin, 3-epi-α-amyrin, 3-epi-β-amyrin, 3α-hydroxytirucall-8,24-dien-21-oic acid and 3α-hydroxytirucall-7,24-dien-21-oic acid; in D. hopkinsii α-amyrin, β-amyrin, lupeol, tirucallol, sitosterol and stigmasterol. Aspects of chemosystematic of the tribe Protieae are discussed.